'Between a Rock and a Hard Place': The Implications of Lost Autonomy and Trust for Professionals at Sea. (August 2019) - Sampson, Helen; Turgo, Nelson; Acejo, Iris; Ellis, Neil; Tang, Lijun
This article describes changes associated with increased bureaucratisation and surveillance in the regulation and management of the 21st century shipping industry. Drawing upon 303 'real-life' vignette-based interviews, it describes how these transformations are experienced by contemporary navigating officers, and engineers, working on commercial cargo vessels. The article draws attention to the dysfunctional effects of distrust in organisations, describing how lost trust and associated fears impact on the decision-making process of officers thereby inducing a degree of organisational paralysis. This finding may be of particular significance to employers who have introduced punishment-centred bureaucratisation in order to improve organisational efficiency and who are concurrently undermining it.